Penerapan Customer Relationship Management (CRM) dalam Meningkatkan Pelayanan Pelanggan pada Bengkel Motor Sena Jaya - Vrisco Seno Aji; Aprilisa Arum Sari; Dwi Hartanti (Pusat Riset dan Inovasi Nasional, 2026)
The development of information technology encourages various companies to continuously improve the quality of service to their customers, including businesses in the field of motorcycle repair shops. Sena Jaya Motorcycle Workshop faces a number of obstacles in managing customer data, recording vehicle repair history, and coordinating communications that have not been managed in an integrated manner, resulting in less than optimal service and difficulty in maintaining long-term relationships with customers. This study aims to design and build a web-based Customer Relationship Management (CRM) system to improve the quality of service at Sena Jaya Motorcycle Workshop, using a system development approach that includes the stages of needs analysis, design, construction, and system testing. The developed system is equipped with various features, including customer data management, recording service history, handling complaints, and monitoring workshop operational activities. The results of the study indicate that the implementation of a CRM system is able to improve the quality of data management, speed up the service process, and facilitate communication between the workshop and customers, which ultimately contributes to increasing overall customer satisfaction and loyalty.